Aku Ingin Seperti Pitung Pada Cerita Bergambar - chaerani, bunga (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
Picture stories can increase children's interest in reading from an early age so that children's brains are stimulated to develop, have higher imagination power, and increase vocabulary in children's speech by providing reading books that attract children's interest according to their age with stories containing various information about life experiences to develop their fantasy power. This research uses qualitative methods with a research type approach that is research-led practice. Where to carry out research in the field first and then apply it in practice to the process of creating Fine Art works in the form of printed illustrated stories. The artist's work in the form of a book entitled